Improved latrine coverage may reduce porcine cysticercosis: a comparative cross-sectional study, Busia County, Kenya 2021 - Chege, Bernard; Ndambuki, Gideon; Owiny, M.; Kiyong'a, Alice; Fèvre, Eric M.; Cook, Elizabeth A.J. (Frontiers Media, 2023)
Introduction: Smallholder pig farming is an important economic activity for many poor, rural communities in developing countries. Porcine cysticercosis is a growing public health risk in countries where pig rearing is popular. A sanitation-based intervention to reduce the prevalence of open defecation was completed in Busia County, Kenya in 2016. We capitalized on this third party intervention to evaluate its impact on porcine cysticercosis prevalence.